Effects of Olympic-style taekwondo kicks on an instrumented head-form and resultant injury measures - Fife, G. P.; O'Sullivan, D. M.; Pieter, W.; Cook, D. P.; Kaminski, T. W. (British Journal of Sports Medicine, 2013)
Objective: The objective of this study was to assess the effect of taekwondo kicks and peak foot velocity (FVEL) on resultant head linear acceleration (RLA), head injury criterion (HIC15) and head velocity (HVEL).